Positive fluid balance predicts mortality in intensive care unit patients - Sulong, Siti Azila (2014)

(untitled)
Background Positive fluid balance is known to be a factor to cause poor outcome in critically ill patients especially in patient with acute kidney injury. The goal of this study is to assess the outcome of positive fluid balance in general patients admitted to intensive care unit, Hospital Sultanah Nur Zahirah. Objectives The main objective is to determine the association of positive fluid balance in causing mortality of the critically patients who were managed in ICU. Methodology This is a retrospective cohort study. The patients who fulfilled the inclusion criteria and were admitted to ICU between April 1st, 2012 and December 31st, 2013 were included in this study. Data were abstracted from the medical record. Univariate analysis and multivariate analysis were carried out to determine the association and the risk ratio of PFB in predicting the death in ICU patients. ROC curve was plotted to assess the optimal cut-off point. Results: A total of 200 patients were recruited for this study from which 40 patients were died and 160 patients were alive during discharge from ICU. More than 90% of the patients were Malays. The mean (SD) age group was 53.4 (18.1) years old. The main reasons for ICU admission were respiratory failure (46%) and septic shock with respiratory failure 51%). Univariate analysis and multivariate analysis showed that those with positive fluid balance of > 1L per day had 4-fold risk of dying as compared to those with average fluid balance of <1L per day (RR=4.0, 95% CI 2.20, 7.36, P <0.01). The ROC curve showed the cut off point for average fluid balance that risk to mortality was 987 ml per day. Conclusion: The average positive fluid balance of >1L per day during ICU stay is a risk factor for mortality among the critically ill patients managed in ICU.